O litoral do Rio Grande do Norte: Dinâmica e modelo espacial - Andrea de Castro Panizza; Jérôme Fournier (Confins)
The northeastern brazillian coast is experiencing rapid land cover changes. The growth of cities, tourism and some prawn fisheries are responsible of these changes, which alter the natural systems and can affect the quality of human life. This work brings part of the research results developed during a post-doctoral position conducted in the laboratory COSTEL (Climat et du Sol Occupation par Télédétection) of the University of Rennes 2 (France) and funded by the CNRS (Centre National de la Recherche Scientifique, France), during the years 2005 and 2006. We propose a study of the dynamic of the landscape of the municipalities of Extremoz, Natal and Parnamirim (State of Rio Grande do Norte, Brazil). The images of the satellites Landsat TM5 and ETM +7 are the main sources used to generate spatial data. We use multi-temporal image, years 1992, 2001 and 2003 to detect land cover changes. We see that the urban and residential has continued to grow during the period study, which represented an expansion of 62 km². Opposite behavior occurred with the classes that represent the vegetalized areas, which have suffered reductions of their areas. This information has been applied in the construction of a spatial model (Brunet, 1980 and 1990) to highlight the basic structures of the geographical area. The graphic representation proposal for the model space highlights the forms and spatial structures, as well as its duties and tries to explain the land cover changes of this area. We note that a fragmented arc surrounding the areas of human occupation, which generate environmental and social problems.